Desain dan Implementasi In-Network Caching Pada Content Centric Networking Menggunakan CCN-Lite Dengan Simulator OMNeT++ - Ibrahim Ibrahim; Achmad Basuki; Eko Sakti Pramukantoro (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Content Centric Networking (CCN) is a proposed architecture for addressing current Internet issues in terms of data distribution. The CCN is content-centric based, where the data search is performed using the name of the content, not the content host. CCN also has a different caching mechanism than caching in general called in-network caching. This study aims to find out how the performance of in-network caching on CCN by design and implementation using CCN-Lite in OMNeT ++ environment. The parameters tested were delivery latency and cache hit ratio (CHR). The result of the simulation is done, the smallest delivery latency is 10.69 ms. This value is obtained from the caching process, when compared with the latency of delivery without caching that is equal to 32.45 ms. It proves that with the caching, the latency gets lower. The highest CHR obtained in the CCNTLV protocol file is 0.54 or 54%, when compared with the CCNB file protocol of 0.45 or 45%. This proves that the higher the value of CHR the better the content is served.